ISO 31000 Risk Management in Practice: Adoption Challenges and Benefits in Qatar’s Leading Construction Firm - Dela Cruz, Gerelyn S.; Ocampo, Alex P. (Future Science / FSH-PH Publications, 2025)
The construction industry frequently faces a range of risks, including safety concerns, financial uncertainty, and operational interruptions that can result in substantial costs. Given these ongoing challenges, adopting a structured approach to risk management has become increasingly important. This study examines the application of the ISO 31000 risk management framework in practice at XYZ Construction in Qatar, with a particular focus on the challenges encountered during implementation and the benefits observed by employees. Data were collected through a structured survey using a convenience sampling method, involving 56 employees from different levels of the organization, to evaluate the effectiveness of the applied risk management practices. The top five benefits identified were enterprise-wide risk perspective, alignment with organizational goals, proactive approach to risk, cost reductions, and increased stakeholder confidence. Nonetheless, implementation faced several barriers, such as knowledge and skills gaps, cultural and operational integration difficulties, limited training and leadership involvement, resistance to change, and inadequate resource allocation. This study utilized multiple regression analysis to investigate the simultaneous influence of various factors on the adoption of ISO 31000. Despite the comprehensive assessment of multiple variables, the findings indicated no statistically significant effect, implying that additional determinants may affect the adoption process. The findings highlight leadership support, clear communication, and strategic planning as vital for embedding risk management. Recommendations focus on targeted training, stronger leadership involvement, tailored risk tools, and improved cross-departmental collaboration to enhance resource allocation, cultural integration, and overall risk management effectiveness.